The molecular interplay among gut dysbiosis, adipose tissue, and metabolite-derived damage-associated molecular patterns in metainflammation and atherogenesis - González-Hermosillo, Leslie Marisol; Ávila-Soto, Karol Iliana; Méndez-García, Lucía Angélica; Cérbulo-Vázquez, Arturo; Esquivel-Velázquez, Marcela; Bueno-Hernández, Nallely; Fonseca-Sánchez, Miguel Ángel; Escobedo, Galileo (Frontiers in Immunology, 2025)
Metainflammation is a low-grade systemic inflammatory response that can persist for months or even years, during which monocytes, macrophages, and other immune cells become hyperactivated, contributing to metabolic disease and atherogenesis. Although we now better understand the role of metainflammation in atherosclerosis, uncertainty persists about how gut dysbiosis, adipose tissue expansion, and metabolite-derived damage-associated molecular patterns (Md-DAMPs) can trigger metainflammation and promote atherogenesis. In this comprehensive review, we summarize the role of gut dysbiosis in lipopolysaccharide (LPS) production, a component of gram-negative bacteria that can trigger metainflammation by stimulating circulating monocytes and tissue-resident macrophages. We also outline adipose tissue expansion as an additional igniter of metainflammation by driving the expression of hypoxia-inducible factor 1α (HIF-1α), a master transcription factor that leads to nuclear factor kappa B (NFκB)-dependent proinflammatory cytokine production. Furthermore, we thoroughly explored the precise nature of Md-DAMPs, including glutamate, bile acids, lipoproteins, short-chain fatty acids (SCFAs), uric acid, and excess glucose, with emphasis on the molecular mechanisms that mediate their roles in metainflammation and atherosclerosis. Finally, we integrate the molecular interplay among gut dysbiosis, adipose tissue expansion, and Md-DAMPs to a scenario in which circulating monocytes, macrophages, and foam cells contribute to atherosclerotic plaque formation, instability, and rupture. In conclusion, the information examined here may help refresh our conceptual understanding of atherogenesis, incorporating novel actors as gut dysbiosis, adipose tissue expansion, and Md-DAMPs in the complex network that leads to metainflammation and cardiovascular disease.